Measurement of the correlation between flow harmonics of different order in lead-lead collisions at sqrt(sNN) = 2.76 TeV with the ATLAS detector - Aad, G. (2015)
Correlations between the elliptic or triangular flow coefficients vm (m = 2 or 3) and other flow harmonics vn (n = 2 to 5) are measured using √sNN = 2.76 TeV Pb+Pb collision data collected in 2010 by the ATLAS experiment at the LHC, corresponding to an integrated lumonisity of 7 µb −1 . The vm–vn correlations are measured in midrapidity as a function of centrality, and, for events within the same centrality interval, as a function of event ellipticity or triangularity defined in a forward rapidity region. For events within the same centrality interval, v3 is found to be anticorrelated with v2 and this anticorrelation is consistent with similar anticorrelations between the corresponding eccentricities 2 and 3. On the other hand, it is observed that v4 increases strongly with v2, and v5 increases strongly with both v2 and v3. The trend and strength of the vm–vn correlations for n = 4 and 5 are found to disagree with m– n correlations predicted by initial-geometry models. Instead, these correlations are found to be consistent with the combined effects of a linear contribution to vn and a nonlinear term that is a function of v 2 2 or of v2v3, as predicted by hydrodynamic models. A simple two-component fit is used to separate these two contributions. The extracted linear and nonlinear contributions to v4 and v5 are found to be consistent with previously measured event-plane correlations